The future of Lenin : power, politics, and revolution in the twenty-first century - Ivanchikova, Alla, 1977-; Maclean, Robert R. (SUNY Press, 2022)
"Situated in a particular historical moment marked by the violent crises of capitalism--the rise of the alt-right, the COVID-19 pandemic, and the Black Lives Matter movement--The Future of Lenin collects essays by an international cohort of scholars to assert Lenin's relevance for twenty-first-century politics and thought. Taking different and sometimes opposing vantage points on Lenin's value for the future, the contributions to this volume reveal an unexpected Lenin, one who escapes the stale Cold War-era discourse of demonization and hagiography. Instead, the future-oriented Lenin in these pages comes to life as our contemporary: an interlocutor who is surprisingly relevant for Black and anticolonial struggles in the US and beyond; for building the new Left; and for assessing Bernie Sanders' movement as well as alt-right anti-statism. In short, Lenin's concrete development of Marxism for his historical conditions may yet offer lessons for revolutionaries to come."-- Provided by publisher.
Keywords: Lenin, Vladimir Ilʹich, -- 1870-1924 -- Influence.; Lenin, Vladimir Ilʹich, -- 1870-1924; World politics -- 21st century.; Politique mondiale -- 21e siècle.; Communism; POLITICAL SCIENCE / Political Ideologies / Communism, Post-Communism & Socialism; 2000-2099